(untitled) (Open Herald: Periodical of Methodical Research, 2024)
This article explores the standardization processes of syrup dosage forms and biologically active additives (BAAs), focusing on their chemical composition, efficacy, and safety. The authors review various methods of standardization, including quality control parameters such as pH, viscosity, and concentration of active ingredients. They also investigate the biological activity of different additives in syrup formulations, providing a comparative analysis of their therapeutic effects, bioavailability, and potential side effects.The study uses both experimental and analytical approaches, comparing commercially available syrups with different biologically active additives. The results highlight the importance of precise standardization to ensure consistency in therapeutic outcomes and consumer safety. The findings also suggest that some formulations may require stricter quality control measures due to variability in the concentration of active ingredients.The article concludes by recommending the adoption of improved regulatory standards for syrup dosage forms containing biologically active additives to enhance product quality and efficacy. Further research is suggested to refine the methodologies for evaluating these products